Analisis Model Bisnis Biogas dari Limbah Ternak Sebagai Solusi Energi Terbarukan di Era Ekonomi Hijau - Mohamad Afrizal Miradji; Putri Mariana; Ayunda Frischa Nadira; Tri Aji Pratomo; M. Rizki Rizal Maulana; Bayu Adi (Kajian Ekonomi dan Akuntansi Terapan, 2025)
The transition to a green economy demands innovation in the utilization of environmentally friendly and sustainable renewable energy sources. This article analyzes a business strategy based on biogas energy from cow dung as an alternative solution in providing renewable electricity. Using a descriptive qualitative approach, this study evaluates the potential, challenges, and business models that can be applied to develop a sustainable biogas business. The findings show that biogas utilization not only contributes to reducing greenhouse gas emissions and managing livestock waste, but also has high economic value if supported by the right business strategy. Key success factors include technological innovation, supporting policies, and access to financing. This article recommends strengthening the community-based renewable energy business ecosystem as a concrete step towards a just and environmentally friendly energy transition..